The influence of density on survival and larval development in the sea urchin arbacia dufresnii (Echinodermata: Echinoidea) - Chaar, Florencia Belén (2021)
Density is one of the critical factors in echinoderm larvae for aquaculture purposes. Echinoplutei larvae are very sensitive to overcrowding. High culture density can lead to problems with bacteria or protozoa, decreasing survival and generating abnormal morphotypes. Objective: To evaluate the effect of culture density on survival and larval growth in the sea urchin Arbacia dufresnii. Methods: Two days after fertilization of A. dufresnii we we kept treatments at 1, 3, 5 and 10 larvae.ml-1, with three replicates each. We recorded survival and abnormal morphotypes periodically, as well as growth:somatic rod length, total length, and length of the post oral arms,. we applied generalized linear models. Results: Survival is dependent on density, time and replicates, and their interactions. Larval growth depended on density and time, also with interaction between the variables. The treatment of 5 larvae.ml-1 had the highest survival and larval condition. Conclusions: Larval culture of A. dufresnii had the best results at 5 larvae.ml-1.